2011
DOI: 10.1093/eurjhf/hfr078
|View full text |Cite|
|
Sign up to set email alerts
|

Brain natriuretic peptide‐guided treatment does not improve morbidity and mortality in extensively treated patients with chronic heart failure: responders to treatment have a significantly better outcome

Abstract: Aim To determine whether brain natriuretic peptide (BNP)‐guided heart failure (HF) treatment improves morbidity and/or mortality when compared with conventional treatment. Methods and results UPSTEP was an investigator‐initiated, randomized, parallel group, multicentre study with a PROBE design. Symptomatic patients with worsening HF, New York Heart Association class II–IV, ejection fraction <40% and elevated BNP levels, were included. All patients (n= 279) were treated according to recommended guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 24 publications
6
107
0
10
Order By: Relevance
“…Consistent with above differences in remodeling indices as a function of NT-proBNP response, there was no significant improvement in diastolic filling indices among nonresponders (E/E′ from 13 [9][10][11][12][13][14][15][16][17] to 12 [10][11][12][13][14][15][16][17], P=.32) while right ventricular systolic pressure (RVSP) was only marginally lowered (from 46AE12 mmHg to 42AE11 mmHg, P=.05). In contrast, there was a significant improvement in responders, with E/E′ decreasing from 10[7-13] to 9 [6][7][8][9][10][11][12] (P=.040) and right ventricular systolic pressure decreasing from 41AE10 mm Hg to 34AE8 mm Hg, (P<.001). NT-proBNP Nonresponse and Clinical Outcomes As expected, patients who began and ended the study with an NT-proBNP 1000 pg/mL had the fewest cardiovascular events (.50AE1.23 event per patient) while those who had an NT-proBNP level >1000 pg/ mL throughout the study had the highest event rates (1.57AE1.9 events per patient, P=.003; Figure S1).…”
Section: Nt-probnp Nonresponse and Echocardiographic Changessupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with above differences in remodeling indices as a function of NT-proBNP response, there was no significant improvement in diastolic filling indices among nonresponders (E/E′ from 13 [9][10][11][12][13][14][15][16][17] to 12 [10][11][12][13][14][15][16][17], P=.32) while right ventricular systolic pressure (RVSP) was only marginally lowered (from 46AE12 mmHg to 42AE11 mmHg, P=.05). In contrast, there was a significant improvement in responders, with E/E′ decreasing from 10[7-13] to 9 [6][7][8][9][10][11][12] (P=.040) and right ventricular systolic pressure decreasing from 41AE10 mm Hg to 34AE8 mm Hg, (P<.001). NT-proBNP Nonresponse and Clinical Outcomes As expected, patients who began and ended the study with an NT-proBNP 1000 pg/mL had the fewest cardiovascular events (.50AE1.23 event per patient) while those who had an NT-proBNP level >1000 pg/ mL throughout the study had the highest event rates (1.57AE1.9 events per patient, P=.003; Figure S1).…”
Section: Nt-probnp Nonresponse and Echocardiographic Changessupporting
confidence: 56%
“…5,6 Elevated NT-proBNP has been validated for its ability to predict adverse outcomes in chronic HF, [7][8][9] and the role of serial natriuretic peptide measurement 9,10 and the novel concept of biomarker response to HF therapy have been introduced. 11,12 While the concept of biomarker-guided HF management has been examined in several trials with various designs, [13][14][15][16][17][18] data are limited on how exactly HF biomarker response should be defined and what biomarker response may mean relative to biomechanical and clinical outcomes. A better characterization of natriuretic peptide response to HF therapy, along with the ability to better understand those patients likely to be a "nonresponder" would be essential knowledge in further studying guided therapy of HF.…”
mentioning
confidence: 99%
“…Positive studies derive almost exclusively from those centers which have treated the overwhelming majority of patients and have published the majority of papers on the argument; most of these authors are members of Working Groups on HF (Table 1). While 6 studies [31,33,41,42,55,56] reported encouraging trends with the NPs-guided therapy in comparison to conventional care, such as reduced events in younger patients or in patients with reduced LV ejection fraction (in these studies a very low NP level was targeted, both in the intervention arm with NP-guided and in arm without NP-guided therapy), other studies [45,[57][58][59] presented neutral results. Results derive from different approaches.…”
Section: Different Results Of Different Studies On Nps-guided Therapymentioning
confidence: 99%
“…Az elmúlt évtizedben számos, nagyon heterogén vizsgálat értékelte a natriureticus peptidek szerepét a króni-kus szívelégtelenség kezelésének irányításában [39,40,41,42,43,44,45,46,47,48]. Bár a legtöbb vizsgálat-ban az értékelt biomarker alkalmas volt a betegek és a betegség súlyosságának követésére, a vizsgálatok egy részében ez nem járt együtt a morbiditás és a mortalitás csökkenésével.…”
Section: A Natriureticus Peptidek Szerepe a Krónikus Szívelégtelenségunclassified